Water footprint of goats slaughtered in the interior of Paraíba in 2016 (Research, Society and Development, 2022)
The objective of the work was, from the concept of virtual water, to calculate the water footprint of goats slaughtered in the interior of Paraíba in the year 2016. For the purposes of the study, the sample was the region of Barracks 04 of Paraíba in the year 2016, for concentrating the largest number of slaughters in the state in just 08 municipalities. The PH calculation was focused on blue water, considering the amount of water intended for watering, irrigation of Buffel and Tifton-85 grass forage and cleaning of the facilities. The highest impact index of the value found was the lack of water, corresponding to more than 80% of the total value. The calculation showed the importance that knowledge on the subject has for the creation of public policies suitable for the management of water resources and for raising the awareness of the goat producer in the studied region, regarding the proper management of the herd with regard to water.